2017
DOI: 10.1021/acs.jafc.6b04903
|View full text |Cite
|
Sign up to set email alerts
|

Intervention of Isomaltodextrin Mitigates Intestinal Inflammation in a Dextran Sodium Sulfate-Induced Mouse Model of Colitis via Inhibition of Toll-like Receptor-4

Abstract: Isomaltodextrin (IMD), a highly branched α-glucan, is a type of resistant starch. Earlier studies have indicated that polysaccharides could prevent inflammation and can be effective in reducing the complications of chronic gastrointestinal diseases such as inflammatory bowel disease (IBD). Therefore, the aim of the present study was to evaluate the anti-inflammatory effect of IMD in dextran sodium sulfate (DSS)-induced colitis in a mouse model. IMD (0.5, 1.0, 2.5, and 5.0% (w/v)) was given orally for 23 days t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 43 publications
(85 reference statements)
2
32
1
1
Order By: Relevance
“…The main benefit of a nutritional diet intervention is taking control of the development of inflammation to promote mucosal healing, with minimal side effects (Galvez, Rodrguez-Cabezas, & Zarzuelo, 2005;Goh & O'Morain, 2003). Research has shown that isomaltodextrin, a fiber-like polysaccharide, alleviates the inflammatory reaction caused by DSS via inhibition of toll-like receptor-4 expression in the colon of mice (Majumder et al, 2017). Dietary supplementation with Astragalus membranaceus and Ganoderma lucidum polysaccharides have a mitigating effect on DSS-induced colitis in mice (Luo et al, 2018;Lv et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The main benefit of a nutritional diet intervention is taking control of the development of inflammation to promote mucosal healing, with minimal side effects (Galvez, Rodrguez-Cabezas, & Zarzuelo, 2005;Goh & O'Morain, 2003). Research has shown that isomaltodextrin, a fiber-like polysaccharide, alleviates the inflammatory reaction caused by DSS via inhibition of toll-like receptor-4 expression in the colon of mice (Majumder et al, 2017). Dietary supplementation with Astragalus membranaceus and Ganoderma lucidum polysaccharides have a mitigating effect on DSS-induced colitis in mice (Luo et al, 2018;Lv et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the rat model, pathological damage of the colon can be evaluated in accordance with literature. Majumder et al has evaluated tissue damage in terms of inflammation, epithelium, glands, depth of lesion, and the extent of the section affected [52]. Zhang et al has assessed histological damage by using a combined score of inflammatory cell infiltration and mucosal damage [53].…”
Section: Discussionmentioning
confidence: 99%
“…The colon was opened longitudinally and flushed with ice-cold normal saline. The intestinal segments were collected at a distance of 6 cm from anus and fixed in 4% paraformaldehyde for 24 h. The fixed samples were then embedded in paraffin wax, stained with H&E for histopathological analysis in accordance with previously published literature [52][53][54] with some modifications. The first step was to observe whether the transverse structure of the colon was intact (intact: 0; mucosa damage: 1; submucosa damage: 2; muscle damage: 3).…”
Section: Induction and Assessment Of Oxz-induced Colitismentioning
confidence: 99%
“…Ayrıca izomaltodekstrin bazı proinflamatuar sitokinlerin gen ekspresyonlarını baskılama, bazı antiinflamatuar sitokinlerin ise gen ekspresyonunu artırma eğilimi göstermiştir. 26 İnflamatuar bağırsak hastalıklarının beslenme tedavisinde dirençli nişasta tüketiminin artırılması, son yıllarda araştırmaların yoğunlaştığı konulardandır. Çalışmalarda çoğunlukla hayvan modelleri kullanılmakla birlikte insan çalışmaları da yapılmaktadır.…”
Section: Dirençli Nişastanın Inflamatuar Bağırsak Hastalıkları üZerinunclassified